Integrating Sustainable Transportation Modes: A Systematic Literature Review of Environmental Impacts - Kemmala Dewi (Science and Applied Journal (SIAP), 2024)
This research aims to investigate the impact of integrating sustainable transportation modes on greenhouse gas emissions, air pollution and environmental degradation in various geographic regions and levels of development. By systematically analyzing relevant literature, this research identifies the factors that influence the effectiveness of sustainable transport mode integration as well as the implications of these findings. Through a systematic literature review method, this research evaluates various studies that have been conducted previously to provide an in-depth understanding of how the integration of sustainable transportation modes can influence these environmental aspects. The analysis results show that the integration of sustainable transportation modes has a significant impact in reducing greenhouse gas emissions and air pollution, especially in urban areas and developed countries. However, significant challenges occur in rural areas and developing countries, where limited transport infrastructure and the habit of using private transport remain major obstacles. The implication of this research is the need for a contextually tailored approach in designing policies and strategies to promote the integration of sustainable transport modes, involving government, transport planning and the private sector.